Postflask management of micropropagated bananas and plantains: A manual on how to handle tissue-cultured banana and plantain plants - Vuylsteke, J.; Talengera, D.; Reeves, J.; Owoeye, T. (International Institute of Tropical Agriculture, 1998)
Micropropagation techniques have the potential to deliver large amounts of propagules of vegetatively propagated plantain and banana, enabling the rapid dissemination of land races and new varieties resulting from breeding programs. However, a critical stage in the realization of this potential is postflask management, in order to rear the in vitro plantlets to a stage where field establishment is assured. This manual provides a stage-by-stage practical guide to postflask management beginning at the first stage of removal from the tissue culture facility through to the final stage of field establishment. The authors have drawn largely upon their own practical experience of this process, working in both lowland and mid-altitude humid environments. It is intended that this manual will be used by the technicians who are practically involved in the dissemination of plantain and banana germplasm.